Słowacki realizm magiczny w polskim przekładzie / Slovak magical realism in polish translation - Buczek, Marta (Przekłady Literatur Słowiańskich, 2009)
The author presents in this paper her consideration of the strategy of translation taken by Jacek Bukowski, polish translator of Václav Pankovčín prose. Short stories Marakéš (1994) and the novel Tri ženy pod orechom (1996) by Václav Pankovčín were publicated in Poland under the title Marakesz (2006) and are the only one example of slovak prose transalted into polish this year. The author of the paper discusses transtlatological problems of the prose wchich strongly corespondents with magical realism, she concentrates on the semantic signals of the text, significant elements of the structure which define the boundary-line of the meaning space of Václav Pankovčín works. Finaly she reflects on the transfer of implicated senses and meanings from original into translation. She reflects how in proces of translation the translator transfered hormony of fundamental codes of the original (lexical, semantics, cultural and estetic).